Coaxial probe ended by a metallic cavity cell to determine the material dielectric constant and dissipation factor - Franck Moukanda Mbango; Micke Ghislain Lountala; Omar Christian Massamba (Measurement: Sensors)
– A new broadband technique based on combining the lumped and distributed elements with the sample under test (SUT) trapped inside the hole of the five-side-closed copper cavity and fed by a flat termination SMA (open-coaxial probe) is developed to determine the dielectric constant (DK) and dissipation factor (DF) and described in this paper. The method novelty expresses the relationship between the effective and relative permittivities through a second-degree polynomial function with three unknown complex coefficients, each of which is dependent on a specific frequency. The technique utilizes only the standard materials DK within a particular range to determine the required coefficients, including probe-cavity interface effects. That's for reaching an expected accuracy better than 5 % on the DK. The method offers the possibility of extracting up to 10−4 DF. The SUT is a square with a side length of 4.1 mm and a thickness of 510 μm. The Fused Quartz and Alumina 99.5 % have been tested in the 0.24–18.0 GHz frequency range, utilizing the measurement bench associated with the vector network analyzer (VNA) radiofrequency equipment. All measurements are made in two configurations: the cavity (trapping device) is filled with vacuum (as a reference), followed by the SUT (sample to be characterized).